2019
DOI: 10.3390/ijms20133331
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Potential of Oligonucleotide Therapeutics against Pancreatic Cancer

Abstract: Although many diagnostic and therapeutic modalities for pancreatic cancer have been proposed, an urgent need for improved therapeutic strategies remains. Oligonucleotide therapeutics, such as those based on antisense RNAs, small interfering RNA (siRNA), microRNA (miRNA), aptamers, and decoys, are promising agents against pancreatic cancer, because they can identify a specific mRNA fragment of a given sequence or protein, and interfere with gene expression as molecular-targeted agents. Within the past 25 years,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 119 publications
(127 reference statements)
0
20
0
1
Order By: Relevance
“…Moreover, the burgeoning SELEX technology makes it possible to select personalized aptamers for each patient. It has been reported that primary cancerous cells and biopsies directly originating from patients have been used for individual tumor-specific aptamer selection ( Liu et al, 2019 ; Takakura et al, 2019 ; Zamay et al, 2019 ). Additionally, organoid technology has become one of the most important breakthroughs, so patient-derived tumoroid-based SELEX is likely to exhibit exciting potential prospects for personalized ApDC treatment.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Moreover, the burgeoning SELEX technology makes it possible to select personalized aptamers for each patient. It has been reported that primary cancerous cells and biopsies directly originating from patients have been used for individual tumor-specific aptamer selection ( Liu et al, 2019 ; Takakura et al, 2019 ; Zamay et al, 2019 ). Additionally, organoid technology has become one of the most important breakthroughs, so patient-derived tumoroid-based SELEX is likely to exhibit exciting potential prospects for personalized ApDC treatment.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Several aptamers are currently in various stages of clinical trials for therapy of hematological [ 1 ] and pancreatic cancer [ 177 ] diseases. Pi et al [ 178 ] also reported preparation of RNA/DNA hybrid nanoparticles that contained DNA aptamer specific to annexin A2 in ovarian cancer cells.…”
Section: Dna/rna Aptamers: Structure and Propertiesmentioning
confidence: 99%
“…Another group reported that AZD9150 increases drug sensitivity and decreases tumorigenicity in neuroblastomas [170]. Recruitment for AZD9150 trials in colorectal, pancreatic, and lung cancer is ongoing (NCT02983578) [171].…”
Section: Therapeutic Options Against Tumorigenic Fam72: Rna Interferementioning
confidence: 99%